Color improvement of rubies by ion beam technique - S. Intarasiri (2018)
© 2016 Elsevier B.V. Ion implantation technique has been used for improving the quality of natural ruby. The implantation was performed by using 90 keV N2-ion and 50 keV O-ion beams. Either kind of ion species could eliminate tiny inclusions in the ruby as observed from an optical microscope. The red color of the ruby was intensified after O-ion implantation. N2-ion implantation changed the color of red ruby to be violet-red. UV–vis and X-ray absorption spectroscopic techniques were employed for investigating the mechanism behind the optical quality improvement of the ruby. The results from both measurement techniques are reported and discussed.